Use of Natriuretic Peptides as a Guidance for Treating Patients with Chronic Heart Failure: Unresolved Issues and Novel Insights - De Vecchis, Renato; Esposito, Claudia (International Journal of Statistics in Medical Research, 2013)
Serial measurements of natriuretic peptides (NPs), i.e. B-type natriuretic peptide (BNP) or amino-terminal fragment of pro B-type natriuretic peptide (NT-pro BNP), may serve as an objective guide to modulate the intensity of drug treatment for individuals with chronic heart failure (CHF). However, considerable uncertainty remains about the alleged useful role of NP-guided therapy in this context. Particularly, which NP level should be assumed as optimal target level for therapy is still matter of debate. Actually, a too low predetermined cut off is encumbered with the risk of inducing a dose escalation perhaps not founded on solid rationale but provided with the potential of propitiating adverse medication effects that may be associated with higher doses. Conversely, a too high predetermined level for NP would entail a poor sensitivity, with the potential of excluding from higher doses of medications, that are proven to increase survival, just the patients who above all would have benefitted from this uptitration. Another much debated issue is constituted by possible age-related differences concerning the effects on clinical endpoints of NP-guided therapy. In addition, some Authors dispute about the possible advantages for the cardiovascular system arising from the functional activation of NPs in CHF patients, so denying that their increased levels have to be per se blamed for hemodynamic upheaval, especially in elder CHF patients. After outlining the main RCTs carried out so far, the Authors stress the above reported issues and discuss the sometime contradictory results of the RCTs exploring NPs use as a guidance for therapy.